Influence of energy-environmental factors on the competitiveness of hydrogen as a motor fuel (in transport energy installations) - Соловей, Віктор Васильович; Внукова, Наталія Володимірівна; Гриценко, Анатолій Володимирович; Каніло, Павло Макарович (Eastern-European Journal of Enterprise Technologies, 2014)
It is described in the paper that for maintaining eco-safe motor transport systems evolution, the development of criteria, based on which it would be possible to evaluate the perfection and technical condition of automobiles is necessary. On the basis of experimental data handling, obtained while testing automobiles of a various make, based on the analysis and coordination of numerous research results, the authors have confirmed that benzopyrene is a reliable indicator of prioritized carcinogenic hydrocarbon emission level and can be used as an indicator of total carcinogenicity () of automobile exhaust gases. Formulas for the calculation are given. The changes in specific cost expenditures () when using hydrogen, as an additional energy carrier were calculated. An assessment of the total energy expenditure and atmospheric emissions when using different fuel technologies in motor transport was made. It is proved that adding hydrogen to the diluted air-fuel mixture in the ICE is economically sound. The expediency of wind-power potential at the self-supporting motorway filling stations was found. It is emphasized that with the full implementation of the mentioned technologies, an increase in socio-economical attractiveness of the hydrogen energetics transport component is expected.